Effect of hydrogen proportion on lean burn performance of a dual fuel SI engine using hydrogen direct-injection. (15th December 2016) - Niu, Renxu; Yu, Xiumin; Du, Yaodong; Xie, Hanguang; Wu, Haiming; Sun, Yao
Highlights: Hydrogen addition improved the burning rate of mixture and flame velocity. Hydrogen acts as a flame kernel while setting fire on mixture. Lean-burn performance gets improved due to extended flammability after hydrogen added. Carbonic emission reduced with additional of hydrogen. Direct injection combined with tumble flow enhanced the effect of hydrogen addition. Abstract: Hydrogen is a fuel that has low ignition energy, wide inflammability limit and superb combustion rate, using hydrogen-enriched gasoline mixture in SI engine is a favorable way to improve the performance of burning process, particularly in lean-burn condition. Hydrogen direct injection allows forming stratified mixture with back fire prevention and independent with intake air content. An experimental investigation was performed to analyze the stratified lean-burn characteristics of a hydrogen-enhanced gasoline engine with hydrogen direct injection. Five different hydrogen additional fractions (3.9%, 5.3%, 7.2%, 8.9%, and 10.5%) were used under four different excess air ratios (1, 1.2, 1.5, and 1.8) with 1500 rpm of engine speed. Hydrogen injection timing was optimized to form a stratified mixture. The result obtained demonstrated that flame developing duration and combustion duration were reduced after hydrogen added, the engine performed higher in-cylinder pressure and heat release rate with the increase of hydrogen proportion as well as effective thermal efficiency. Due to the improvement on combustion rate, the MBT was retarded close to the TDC. Cyclical variation was reduced and lean-burn limit was extended. In addition, HC and CO emissions were reduced while NOx emission increased with addition of hydrogen. The PM emission remains a low level.